COVID-19 Seroprevalence and PLHIV: COVID-19 Seroprevalence and PLHIV (Actualizaciones en Sida e Infectología, 2021)
It is not known whether people living with HIV (PLHIV) are at increased risk of acquiring SARS-CoV-2 infection. Prospective serological studies can allow seroincidence analysis. This prospective study included PLHIV, without a history of vaccination against SARS-CoV-2, from the Autonomous City of Buenos Aires (CABA) and Buenos Aires surroundings (GBA), who attended INBIRS Institute between March and June 2021 to carry out their controls. The seroprevalence rate of antibodies against the SARS-CoV-2 spike protein was 33.3% (CI 24.9-42.5%) for the study population. This prevalence was significantly higher than that previously reported for the general population of the same geographic region. No association was found between CD4+ T-cell counts with levels of SARS-CoV-2 specific IgG. In conclusion, the finding of a high seroprevalence of antibodies against SARS-CoV-2 among PLHIV in CABA and GBA may suggest a greater susceptibility to infection; however, it can also be a surrogate marker that the seroprevalence rate in the general population is underestimated.
Keywords: COVID-19, HIV, seroprevalence